2023
DOI: 10.3390/molecules28124828
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Purification, Structural Characteristics, Health Benefits, and Application of the Polysaccharides from Lonicera japonica Thunb.: A Review

Xinpeng Yang,
Aiqi Yu,
Wenjing Hu
et al.

Abstract: Lonicera japonica Thunb. is a widely distributed plant with ornamental, economic, edible, and medicinal values. L. japonica is a phytoantibiotic with broad-spectrum antibacterial activity and a potent therapeutic effect on various infectious diseases. The anti-diabetic, anti-Alzheimer’s disease, anti-depression, antioxidative, immunoregulatory, anti-tumor, anti-inflammatory, anti-allergic, anti-gout, and anti-alcohol-addiction effects of L. japonica can also be explained by bioactive polysaccharides isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Monosaccharides are the basic units and components of polysaccharides [41,42]. C. speciosa polysaccharides are first hydrolyzed into monosaccharides by acid hydrolysis.…”
Section: Monosaccharide Compositionsmentioning
confidence: 99%
“…Monosaccharides are the basic units and components of polysaccharides [41,42]. C. speciosa polysaccharides are first hydrolyzed into monosaccharides by acid hydrolysis.…”
Section: Monosaccharide Compositionsmentioning
confidence: 99%
“…The flower, buds and caulis of JYH is determined as only plant sources widely used for in Chinese Pharmacopoeia [2]. Modern pharmacological studies have shown that JYH has broad pharmacological properties, including antioxidant, antiviral, antiseptic, and anti-inflammatory effects [3][4][5]. More than 300 medicine compounds have been reported in the buds and flowers of JYH and investigated their biosynthesis and pharmacological activities [6].…”
Section: Introductionmentioning
confidence: 99%
“…Its dry flower buds, leaves, and stems are rich in flavonoids, polysaccharides and other components, which have a broad spectrum of antioxidant, anti-carcinogenic, anti-inflammatory, and anti- bacterial effects ( Yang et al, 2017 ; Tang et al, 2021 ). L. japonica extract is widely used in cosmetics, pharmacological preparations, food, and animal husbandry ( Li et al, 2020 ; Zhang X. et al, 2022 ; Yang et al, 2023 ). L. japonica has strong adaptability ( Thanabhorn et al, 2006 ; Yan et al, 2016 ), is tolerant of severe cold and drought, and does not require high soil nutrient conditions.…”
Section: Introductionmentioning
confidence: 99%